FACTORS ASSOCIATED WITH PARTICIPATION OF NURSES IN EARLY DETECTION OF CERVICAL CANCER - Putu Inge Ruth Suantika; Yanti Hermayanti; Titis Kurniawan (Belitung Raya Foundation, Indonesia, 2019)
Background: The number of cervical cancer still remains high among women, including nurses in Indonesia. This is due to low participation of them to early detect and prevent it.Objective: This study aimed to identify the factors associated with the participation of nurses in early detection (pap-smear test) of cervical cancer at the hospitals in Bandung Indonesia.Methods: This was a correlational study with a cross-sectional approach on 286 nurses selected using cluster sampling at three hospitals in Bandung on March 2018. Data were collected using health belief model (HBM) questionnaire. Data were analyzed using Chi-square or Fisher exact and multivariate logistic regression test.Results: Factors associated with pap-smear behavior were the level of education, perceived susceptibility, perceived barrier and self-efficacy (p-value <0.05). Perceived susceptibility was the most correlated factor with pap-smear behavior with relationship strength (OR) of 16.259 and gave an effect of 27.89% as illustrated in the model equation of y = 0.324 + 2.789 susceptibility + 2.738 barriers.Conclusion: Pap smear behavior of the nurses was still relatively low because they had a negative perception of susceptibility to cervical cancer. Therefore, information is needed to change the nurses' perception related to the susceptibility of symptoms and risk factors that encourages nurses to do the pap-smear and increase nurses' awareness to actively participate in cervical cancer prevention program.